ANALISIS GAYA KOMUNIKASI KEPEMIMPINAN GANJAR PRANOWO SELAKU GUBERNUR JAWA TENGAH - Helena Christine Dora; Linus Kali Palindangan (Jurnal Ilmu Komunikasi Widyanita, 2024)
This research is motivated by the style of communication delivered by Ganjar Pranowo who is the Governor of Central Java. This is because Ganjar Pranowo uses and utilizes social media to communicate which shows that he is a figure who keeps up with the times. In addition, good communication skills were also shown by Ganjar Pranowo with the younger generation in Indonesia. The purpose of this research is to find out the leadership communication style of Ganjar Pranowo as the Governor of Central Java in terms of direct communication with his staff and to find out the communication style of Ganjar Pranowo's leadership as the Governor of Central Java to his people. This study uses qualitative methods by collecting data through observation, interviews and documentation. The results of this study are that of the six types of communication styles, Pak Ganjar has five communication styles, namely the controlling style, the equalitarian style, the structuring style, the relinguishing style and the dynamic style. Based on these five communication styles, the communication style acknowledged by the informants regarding Mr. Ganjar's communication style is the relinguishing style, this communication style is the availability of Mr. Ganjar in accepting other people's suggestions, opinions or ideas. There is one communication style that Pak Ganjar does not have, namely the withdrawal style.